Intervenciones de cuidado para promover el desarrollo del proyecto de vida en personas mayores: una revisión integrativa de la literatura (2025)
The life plan of older adults is a key element in promoting active and healthy aging, as it contributes to maintaining autonomy, identity, and a sense of purpose during this vital stage. However, aging often entails challenges such as cognitive decline, functional limitations, and psychosocial factors that affect overall well-being.